2010
DOI: 10.1016/j.freeradbiomed.2010.09.020
|View full text |Cite
|
Sign up to set email alerts
|

The pro-oxidant chromium(VI) inhibits mitochondrial complex I, complex II, and aconitase in the bronchial epithelium: EPR markers for Fe–S proteins

Abstract: Hexavalent chromium [Cr(VI)] compounds (e.g. chromates) are strong oxidants that readily enter cells where they are reduced to reactive Cr species that also facilitate reactive oxygen species (ROS) generation. Recent studies demonstrated inhibition and oxidation of the thioredoxin system, with greater effects on mitochondrial thioredoxin (Trx2). This implies that Cr(VI)-induced oxidant stress may be especially directed at the mitochondria. Examination of other redox-sensitive mitochondrial functions showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 101 publications
(159 reference statements)
3
30
0
Order By: Relevance
“…In our study, we observed no significant change in the g =2.023 signal representing the 3Fe-4S cluster, S3, of complex II with IR. In contrast, results of Myers et al [42] reported a decrease in the aconitase signal (with the same g value) following oxidative stress with chromium radicals. There was a significant increase in the amount of the EPR detectable UQ • radical during ischemia, and this was reduced by reperfusion as well as by Ran treatment.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In our study, we observed no significant change in the g =2.023 signal representing the 3Fe-4S cluster, S3, of complex II with IR. In contrast, results of Myers et al [42] reported a decrease in the aconitase signal (with the same g value) following oxidative stress with chromium radicals. There was a significant increase in the amount of the EPR detectable UQ • radical during ischemia, and this was reduced by reperfusion as well as by Ran treatment.…”
Section: Discussionmentioning
confidence: 61%
“…EPR signals were obtained by scanning the samples in a high intensity magnetic field (3000-4000 G) at 10 Kelvin, 9.6 GHz, 5 mW microwave power and 5 G amplitude modulation. Each sample was scanned 9 times and spectra were averaged [41, 42]. Signal intensities were measured for g’ s of 2.023 (3Fe-4S attributed to cluster S3 of complex II, or to mitochondrial aconitase), 2.006 (attributed to semi-ubiquinone radical, UQ • ), 1.94 (2Fe-2S attributed to N1b of complex I, or to S1 of complex II), and 1.89 (4Fe-4S attributed to N4 of complex I, or to the Rieske center of complex III [43].…”
Section: Methodsmentioning
confidence: 99%
“…The spin-Hamiltonian parameters, midpoint potentials and relaxation behavior of these centers have been reasonably well characterized (6987), along with some other tissue-specific signals from transferrin, ceruloplasmin, and catalase (8890). Specific applications of EPR to mitochondria have included detection of an irreversible deficiency in Complex I FeS clusters in iron-deficient rats (91), heme-nitrosyl in substantia nigra of Parkinson’s diseased brain (92), chromium-dependent inhibition of Complexes I & II and aconitase (93), cardio- and neuro-protection against doxorubicin (80), prophylaxis against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine in a Parkinson’s mouse model (82), the differential sensitivity of aconitase and FeS clusters from Complexes I & III to oxidative and nitrosative stress in heart (94), and the sensitivity of Complex III FeS clusters in aging heart to ischemia (95). However, despite these successes in mechanistic studies, the authors are unaware of any direct application of EPR for functional pathophysiologic studies in humans or whole animal models with primary mitochondrial disease; the closest analog is a study in which a comparison of EPR signals from muscle biopsies of sepsis patients indicated significant depletion of Complex I FeS signals in those who died compared to survivors (86, 96).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophoretic mobility of HMW-AST was greater than that of LMW-AST ( Figure 1B Liver LMW-AST isoenzyme activity dropped in rats treated for 15 days and increased in the 45-day and 60-day groups ( Figure 4A). We believe that these differences between the groups are related to lower mitochondrial oxygen consumption, attenuated gene expression in short-term exposure (15,16), and increased mitochondrial/microsomal lipid peroxidation, cellular induction, and failure in membrane integrity in longer exposures (17).…”
Section: Discussionmentioning
confidence: 96%